The rise of China and international law : taking Chinese exceptionalism seriously - Cai, Congyan (New York, NY : Oxford University Press, 2019)
The rise of China signals a new chapter in international relations and international law. How China interacts with the international legal order - namely, how China utilizes international law to facilitate and justify its rise and how international law is relied upon to engage a rising China - has invited growing debate among academics and those in policy circles. This text provides a systematic and critical elaboration of the interplay between a rising China and international law.
Also issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on September 18, 2019).
Keywords: International law -- China; International and municipal law -- China; China -- Foreign relations -- 1976-; Exceptionalism -- China